Taylor Formula with Remainder Term Evaluated under a Weight Factor at Fluctuationlessness Limit - (:unkn) unknown (AMER INST PHYSICS, 2011)
Taylor expansion of a weighted function is taken into consideration. Fluctuationlessness theorem is applied to the remainder term in integral form and finally an expression which provides an approximation method to a family of non-analytic functions is obtained.
Keywords: Approximation Methods; Taylor Polynomials; Fluctuation Expansion; Non-analytic functions; EXPANSION